Harnessing community science to conserve and study ground-nesting bee aggregations - Kueneman, Jordan G.; Dobler, Cassidy N.; Danforth, Bryan N. (Frontiers in Ecology and Evolution, 2024)
Protecting diverse solitary ground-nesting bees remains a pivotal conservation concern. Ground-nesting bees are negatively impacted by anthropogenic land use change that often removes suitable nesting habitat from the landscape. Despite their enormous ecological and agricultural contributions to pollination, solitary, ground-nesting bees are often neglected, partly due to the significant obstacle of discovering exactly where these bees establish their nests. To address this limitation, we have developed a ‘community science’ project to map aggregations of ground-nesting bees globally. In certain locations, their abundances reach astounding levels, sometimes in the millions, but are scarcely known. Utilizing the iNaturalist platform, which permits geo-referencing of site observations and bee identification, we are providing public education and seeking public engagement to document bee aggregations in order to understand the nesting requirements of diverse species and open new opportunities for their conservation. Conservation priorities may then unequivocally be directed to areas of high species richness, nest densities, and nesting sites of rare bees. Such community-led efforts are vital for successful long-term management of native bees and the biotic and abiotic landscape data from nest-site localities can allow modeling to predict nest-site suitability and to readily test such predictions on the ground. Here, we summarize the progress, current limitations, and opportunities of using a global mapping project (GNBee) to direct conservation efforts and research toward solitary ground-nesting bees.